Synergistic effects of new gentamicin-N.sativa emulsion against gentamicin-resistant, biofilm bacteria of osteomyelitis - Yaacob, Khairul Ikhwan; Yusof, Fatin Athirah; Mohd Yusof, Nazri; Mohamed, Farahidah; Mohd Shafri, Mohd Affendi (2014)

(untitled)
Biofilm bacteria complicate treatment of osteomyelitis by providing resistant to antibiotics, requiring high doses of 10 to 100 times of standard antibiotic treatment. This high leads several adverse effects and toxicity. To overcome these challenges, Gentamicin and Nigella sativa, a natural product with antimicrobial property, are fused in an emulsion. Four emulsions (A,B,C, and D) (containing 0.1% w/v Gentamicin and N.sativa oil concentration between 32.5% v/v to 46.6% v/v) were tested against common osteomyelitic, gentamicin-resistant, biofilm bacteria namely S.aureus, S.epidermidis and P.aeruginosa. Test bacteria were isolated by sonicating clinical samples (Hospital Tengku Ampuan Afzan, Kuantan) and identified using colony morphology, biochemical test and API identification system (Bioemeriuex). Each strain was then tested for biofilm producing ability, followed by sensitivity testing to gentamicin. Antimicrobial susceptibility testing was performed using Disc Diffusion Assay by loading 20µl of test product in blank disc placed on a plate that had been spread with test bacteria. Zone of inhibition was measured after 24 hours incubation. Finally, biofilm formation inhibition was evaluated by transferring emulsions (20µl), test bacteria (100µl) and broth (80 l) per well of a 96-well culture plate and incubated for 24 hours at 37°C. After incubation, wells were decanted, washed 3 times with phosphate buffer solution, stained with 1% crystal violet before OD readings were collected using microplate reader. Results are analyzed using one way ANOVA. Emulsions were compared against N. sativa alone, Gentamicin alone, and untreated sample as controls. The result of disc diffusion, indicated by diameter of zone of inhibition, revealed that significant different are seen against Gentamicin (Tukey’s, p value < 0.05, all emulsions) and N. sativa alone (Tukey’s, p value < 0.05, emulsions A and C) against S.aureus and S.epidermidis. In inhibiting biofilm formation, both emulsions and N. sativa alone have significant activity in comparison to Gentamicin (Tukey’s, p value < 0.05). No activity was exhibited against P.aeruginosa. In conclusion, significantly improved anti-microbial and anti biofilm effects are seen against S.aureus and S.epidermidis but not P.aeruginosa, hence the emulsions have a good prospect to be used future as an effective treatment against some gentamicin-resistant, biofilm bacteria.